Empowering onshore wind energy: A national choice experiment on financial benefits and citizen participation. (February 2023) - le Maitre, Julia; Ryan, Geraldine; Power, Bernadette; O'Connor, Ellen
Abstract: This paper examines a representative choice experiment for Ireland (n = 1014) to understand the trade-offs citizens are willing to make between the distribution of financial benefits from a nearby wind farm and procedural measures for citizen participation in decision-making. Both participatory processes and outcomes which recognise local impacts are necessary for the acceptance of onshore wind farms. This paper distinguishes between shared community benefit funds, near-neighbour compensation, and citizen investment relative to issues of ownership, modes of engagement and the management of financial benefits during siting, construction, and operation of a wind farm respectively. Citizens willing to accept place greater importance on factors associated with distributive and procedural justice, while proximity and related visual impacts have comparatively more importance for citizens unwilling to accept. Willingness to accept is associated with early, in-person, engagement with a community liaison officer during siting and citizen participation in the governance and distribution of financial benefits during operation. However, citizens who show conditional support for wind farm developments prefer compensation of near-neighbour households, semi-state developers, and town hall engagement meetings. Strong supporters are more influenced by financial benefits for the wider community and local (co-)ownership of wind farms, particularly joint ventures between the developer and community. Highlights: 87% of those surveyed (n = 1014) are willing to accept wind farm developments in Ireland. Those less willing to accept prefer semi-state projects and near-neighbour payments. Citizen participation and benefits are more important to those willing to accept. Strong supporters prefer shared financial benefits and joint ownership. Recommendations include local governance of funds and a role for liaison officers.